AQUIFER IDENTIFICATION IN OPAK FAULT ZONE AFTER YOGYAKARTA EARTHQUAKE 2006 WITH SCHLUMBERGER CONFIGURATION GEOELECTRIC METHOD - Prihastiwi Fifi; wibowo Nugroho Budi; Darmawan Denny (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
This research was aimed to determine resistivity values of aquifer constituent rocks, and todetermine aquifer characteristics and hydrostratigraphy in Opak fault zone. The location of researchwas at Opak fault line Paten subvillage, with geographical coordinate of 7°55'18,39'' S to 7°57'09,72''S and 110°19'22,26'' E to 110°22'56,06'' E. The method used was Schlumberger configurationgeoelectric method. Geoelectric method was one of the geophysics method which study earthelectricity based on the Ohm’s Law, by injecting a current through two current electrodes, thepotential different appeared from two potential electrodes can be measured. The data acquisition usedNaniura NRD 22S resistivitymeter. Number of sounding point were 3 points spaced by 10 meters andmeasurement line length was 160 meters. Measurement results were analized using curve matchingmethod by IPI2win software determine subsurface layers based on resistivity. Results showed thatresistivity aquifer constituent rocks are about 19,3-300 Ωm which are sands, gravels, sandstones rocktypes at 5-30 meters depth.Keywords: Geoelectric Method, Aquifer, Paten Subvillage